Molecular characterization of soil-borne viruses infecting sugar beet in Europe and USA - Poimenopoulou, Efstratia (SLU/Department of Plant Biology (from 140101), 2017)
Beet necrotic yellow vein virus (BNYVV, Benyvirus) is the causal agent of rhizomania disease. BNYVV and Beet soil-borne mosaic virus (BSBMV, Benyvirus) share high similarity in their genome organisation. These viruses as well as Beet virus Q (BVQ, Pomovirus) and Beet soil-borne virus (BSBV, Pomovirus) are vectored by the plasmodiophorid Polymyxa betae. BNYVV P25 protein has been reported to be associated with the development of rhizomania disease, thus being a virulence factor of the virus. Recently, resistance breaking isolates of BNYVV have been reported in the Netherlands and the United Kingdom. Additionally, BSBMV has been observed in USA in the fields where BNYVV is not present. In order to understand the dynamics of the viruses associated with rhizomania in the crop, sugar beet plants were baited with soils containing P. betae from USA, the Netherlands, Germany, France and Sweden. BNYVV, BSBMV, BVQ and BSBV were detected by RT-PCR from total RNA isolated from root tissue of the plants. P. betae was detected in samples from all the soils, as well as BSBV. BNYVV was detected in all the samples except for root samples growing in soils from USA, which only showed presence of BSBMV. BVQ was only detected in samples from German, Dutch and Swedish soils. Amino acid sequences of the 'tetrads' of the BNYVV P25 protein from isolates from Germany, Sweden, the Netherlands, and France were found to have the following amino acid sequences: AYHR, AYHR, AYPR and SYHG, respectively. These differences in the tetrad sequence of P25 might be associated with the resistance breaking events by the BNYVV isolates from the Dutch soil, which need further study. Amplifications of full-length RNA 2 of BSBMV revealed the presence of additional RNA species. These species appeared to represent chimeric RNAs characterized by the presence of complete RNA 2 ORF for the coat protein in the 5’-terminus fused to the 3'-untranslated region of either RNA 3 or RNA 4. The presence and accumulation of chimeric RNAs were confirmed by qRT-PCR. Notably, the levels of chimeric RNAs were up to 20-fold higher as compared to accumulation of BSBMV RNA 2. The influence of the chimeric RNAs on the expression of viral symptoms and accumulation of BSBMV remains to be studied.